Clues of pre-illustrated thought in Francisco Suárez: on the equality of sexes - Burlando, Giannina (Anales del Seminario de Historia de la Filosofía, 2022)
An attempt is made to recognize the coherence of Suárez's political postulates and his anthropology. For this purpose I translate a selection of texts, mainly from the third Book of the De opere sex dierum, which gives testimony of the foundations that reveal not only indications of a thought pre-illustrated in Suárez, but the relevance of topics found in his writings that remain to be explored in any of its volumes. I have divided this work into two sections: The first makes brief mention of the defense of the equality of the sexes in François Poullain de la Barre. Furthermore, it refers to the political virtue of Descartes and his defense of the difference of the sexes. The crucial section exhibits forgotten arguments from Suárez's treatise De opere sex dierum, where the question of the equality of the sexes is addressed.
Keywords: Suárez; defense; equality of sexes; De opere sex dierum